The Impact of High-Speed Rails on Urban Consumption—From the Perspective of “Local-Adjacent” Effect - Cai, Wendi; Wu, Zongfa; Lu, Yurong (Frontiers in Environmental Science, 2022)
Under the background of the rapid development of high-speed rail(HSR), the urban spatial distance has been significantly compressed. Exploring the impact of high-speed railway on urban consumption from a spatial perspective is conducive to further understanding and clarifying the spatial economic effects caused by the opening of high-speed railway, and providing scientific basis for the future spatial layout of high-speed railway. Based on the panel data of prefecture-level cities from 2008 to 2018, the spatial spillover effect of high-speed railway on urban consumption is explored and decomposed by building a spatial econometric model. The results show that urban consumption shows significant spatial correlation, and the conclusion is still valid under three different forms of spatial weight matrices. In addition, the high-speed railway network has a positive effect on local urban consumption, and acts on cities in neighboring areas through spatial spillover effect. Further analysis shows that the spillover effect has an effective radius of 100-500 km, which is inverted U-shaped with distance, and 300 km from the central city is the optimal radius.